Pengaruh Penggunaan Media Pembelajaran Canva Berbasis Etnomatematika pada Pelajaran Matematika Sekolah Dasar - Eny Wijayanti; Nurul Choirina; Sukiyanto Sukiyanto; Pardimin Pardimin (Ideguru: Jurnal Karya Ilmiah Guru, 2025)
Mathematics is still not yet contextual so that the learning outcomes have not reached the proficient category. That was one of the reasons why students learning outcomes need to be improved, especially in elementary school. This study aim to examine the effectiveness of using ethnomathematics based canva learning media on mathematics learning in grade fourth elementary school. Quantitative and qualitative descriptive method have used. The data subject came from 10 students on fourth grade of Sidoharjo state elementary school. Data on students activities is obtained through observation during learning and test are used to measure cognitive succes. The data analysis used quantitative and qualitative tehniques. From the data, student motivation and learning outcomes are increased. The increase in mathematics learning outcomes for the material on decomposition and composition of two dimentional figure has increased by 29%. During the initial test, the learning outcomes was 48%, after undergoing treatment it became 77%. This data acquisition is seen from comparison before and after using ethnomathematics based canva learning media. From the SPSS 26 analysis, it was also conclude increased. The increase student’s learning motivation can be seen from actively and enthusiastic student to completing assigments. This shows effectiveness the use of ethnomathematics based canva could improve motivation and the learning outcomes student in fourth grade elementary school.